Realignment of Identity: A Study of Socio-Cultural Ecofeminism in Rita Chowdhury‟s Chinatown Days - Sangeetha , R.K.; P. , Rathna (International Journal of Psychosocial Rehabilitation, 2020)
A woman’s identity changes due to various circumstantial issues such as marriage, childbirth, employment, and so on. In addition to these cultural and social factors, environmental changes such as natural calamities and manmade disasters also effectuate identity changes in women. Some of the major impacts of environmental changes are migration, slave trade, cultural resistance, nationality changes, and statelessness. The novel Chinatown Days (2018) is clear evidence for the identity crisis faced by women due to patriarchal and political upheavals. The author, Rita Chowdhury, not only reveals the changes in women’s identity but also reveals the identity changes in nature due to social and cultural dominance. This paper aims to explore how environmental changes affect both women and nature equally and how the identities of women and nature have been realigned by three dimensional factors—social, cultural, and natural and man-made environmental factors—with reference to Rita Chowdhury’s Chinatown Days through the lens of socio-cultural ecofeminism.